The US Foreign Policy towards China during Trump Administration (Department of International Relations, Universitas Brawijaya, 2023)
To analyze the administration's Asia-Pacific strategy, its implementation is addressed, with the Trans-Pacific Partnership as the most essential part. When the PRC strengthened under Xi Jinping, China's aspirations and reaction to Obama's policies were to examine the potential of more engagement and the Sino American relationship as Trump assumed office in 2017. Trump maintained a combative foreign policy against China, eschewing dialogue. Trump's rejection of the Trans-Pacific Partnership, which was Obama's most important Asia-Pacific policy, his tariffs on Chinese exports, which sparked a trade war, and his attempt to halt Huawei's 5G network for allegedly being a Chinese spying instruments are all relevant issues. The Trump administration wanted to pursue the same ends as the engagement strategy, but through confrontation rather than engagement; to decouple from China, persuade other nations to join America in opposition to China, and bring about a Cold War-like world; or if US foreign policy had shed its idealism, putting